2019
DOI: 10.3892/ijmm.2019.4379
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of sphingosine kinase�1 contributes to�ventilator-associated lung injury in a two-hit model

Abstract: Ventilator-associated lung injury (VALI) remains a significant medical problem in intensive care units. The present study aimed to investigate the role of sphingosine kinase 1 (SPHK1) in VALI using a two-hit model and explore the potential underlying molecular mechanism. Mice were divided into five groups: i) Non-ventilated group; ii) non-ventilated + lipopolysaccharide (LPS) group; iii) ventilated group; iv) ventilated + LPS group; and v) ventilated + LPS + SPHK1 inhibitor group. Mice were administered LPS (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…S1P levels in lung tissues and BALF, not in plasma, were upregulated in intratracheal (IT) LPS-induced acute lung injury [93]. Plasma S1P was increased in a two-hit model induced by intraperitoneal (IP) LPS combined with ventilation [94]. A recent study found that Pseudomonas aeruginosa challenge increases S1P levels in lungs and BALF [95].…”
Section: Protective Role Of S1p In Experimental Acute Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…S1P levels in lung tissues and BALF, not in plasma, were upregulated in intratracheal (IT) LPS-induced acute lung injury [93]. Plasma S1P was increased in a two-hit model induced by intraperitoneal (IP) LPS combined with ventilation [94]. A recent study found that Pseudomonas aeruginosa challenge increases S1P levels in lungs and BALF [95].…”
Section: Protective Role Of S1p In Experimental Acute Lung Injurymentioning
confidence: 99%
“…In addition to its anti-acute lung injury property, SphK1 has been reported to contribute to the pathogenesis of lung injury. IP administration of SphK1 inhibitor exhibited protective effects on the two-hit (ventilation + IP LPS)-induced acute lung injury [94]. Gutbier B et al reported that SphK1-deficient mice had reduced lung hyperpermeability in a P. aeruginosa-induced murine model of acute lung injury [101]; however, another controversial study demonstrated that SphK1 knockout had no effects in P. aeruginosa-induced acute lung injury [95].…”
Section: Protective Role Of S1p In Experimental Acute Lung Injurymentioning
confidence: 99%
“…Given the increased rate of thrombosis in COVID-19, the status of TFPI needs to be investigated with VPA-treatment. The VPA-induced downregulation of SPHK1 appears to help COVID-19 treatment as followed: SPHK1 is known to contribute to ventilator-associated lung injury [46]; elevated SPHK1 enhances influenza virus infection [47]; SPHK1 also serves as a pro-viral factor by regulating viral RNA synthesis and nuclear export of viral ribonucleoprotein complex upon influenza virus infection [48]. VPA-induced downregulation of SPHK appears to be helpful in the treatment of COVID-19 patients.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of RhoA induces the phosphorylation of MLC and contraction of ECs, resulting in gap formation and increased endothelial permeability ( Liu et al, 2013 ). Rock inhibitor could attenuate CS-induced lung endothelial hyperpermeability and the phosphorylation of myosin phosphatase target subunit 1 in vivo and in vitro ( Wang et al, 2019 ). 1-palmitoyl-2-arachidonoyl-snglycero-3-phosphatidyl choline showed a protective role of stretch-induced barrier-disruptive via triggering Rac activation ( Birukova et al, 2011 ).…”
Section: Molecular Mechanisms In Endothelial Permeabilitymentioning
confidence: 99%